An empirical analysis of profit-and-loss sharing financing in Indonesian Islamic banks - Suman, Agus; Supriani, Indri; Rajasa, Muhammad Attar Indra; Anisa, Vera Novia (Faculty of Economics, Universitas Islam Indonesia, 2026)
Purpose – This study examines the determinants of profit-and-loss sharing (PLS) financing adoption in Indonesia by incorporating bank-specific, macroeconomic, and religiosity variables.Methodology – Utilizing monthly time-series data from October 2014 to October 2023, this research employs the Autoregressive Distributed Lag (ARDL) approach to model both long-run and short-run relationships. The analyzed variables include PLS financing, non-performing financing (NPF), capital adequacy ratio (CAR), total assets (TA), Zakat, Infaq, and Shadaqah (ZIS), the Islamic financing rate, the exchange rate, inflation, and the Industrial Production Index (IPI).Findings – The results indicate that in the short run, PLS financing is significantly influenced by CAR, TA, ZIS, and IPI. In the long run, however, PLS financing is predominantly determined by internal banking factors, specifically CAR and TA. Bank capitalization and asset size are critical to PLS financing dynamics, ensuring stability and responsiveness to internal financial conditions, thereby enhancing its viability within Indonesia’s dual banking system.Implications – The findings suggest that Indonesian regulators and bank policymakers should focus on enhancing the long-term availability of PLS-based financing, establishing standardized monitoring frameworks, and improving financial transparency. Furthermore, fostering innovation in Sharia-compliant products and investing in capacity-building initiatives that integrate Islamic jurisprudence with modern finance are recommended to strengthen the sustainability and competitiveness of PLS financing.Originality – This study contributes to the literature by providing an integrated empirical analysis of both internal bank-specific and external macroeconomic determinants of PLS financing in Indonesia, a comprehensive approach rarely explored in prior research.